KELAYAKAN MEDIA POSTER ORGAN TUMBUHAN DENGAN TAMBAHAN TIPE STOMATA 12 TANAMAN - Aspandi, Aspandi; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility of plant organ poster media with the addition of stomata types of 12 plant species. This research was a descriptive study using purposive sampling technique. The poster was validated in two stages, namely instrument validation and poster media validation with four aspects, namely format, content, language and effectiveness. The poster media criteria were validated by five validators consisting of two biology education lecturers at FKIP Tanjungpura University and three high school biology teachers in Pontianak. Data from poster media validation were analyzed using Content Validity Ratio (CVR) formula and Content Validity Index (CVI). The results of the poster media validation obtained CVR and CVI values of 0.89. Thus, the poster was categorized to be valid and feasible to be used as a learning medium in the structure and function of plant tissue material of class XI in high school.Â Keywords: feasibility, poster, stomatal types, validation